2019
DOI: 10.1038/s41398-018-0308-2
|View full text |Cite|
|
Sign up to set email alerts
|

Epistasis of HTR1A and BDNF risk genes alters cortical 5-HT1A receptor binding: PET results link genotype to molecular phenotype in depression

Abstract: Alterations of the 5-HT1A receptor and BDNF have consistently been associated with affective disorders. Two functional single nucleotide polymorphisms (SNPs), rs6295 of the serotonin 1A receptor gene (HTR1A) and rs6265 of brain-derived neurotrophic factor gene (BDNF), may impact transcriptional regulation and expression of the 5-HT1A receptor. Here we investigated interaction effects of rs6295 and rs6265 on 5-HT1A receptor binding. Forty-six healthy subjects were scanned with PET using the radioligand [carbony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…Although the twin sample is valuable for behavioral genetic studies, it is still rare in molecular genetic analyses. Nevertheless, these results represent the robust confirmation of previous findings on non-twin samples (Hahn et al, 2013;Kautzky et al, 2019;Laasa et al, 2017;Reuter et al, 2006), which is important for the process of validating the scientific results which associate specific genes with complex behaviors. An important limitation of the study may be related to the number of gene polymorphisms analyzed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the twin sample is valuable for behavioral genetic studies, it is still rare in molecular genetic analyses. Nevertheless, these results represent the robust confirmation of previous findings on non-twin samples (Hahn et al, 2013;Kautzky et al, 2019;Laasa et al, 2017;Reuter et al, 2006), which is important for the process of validating the scientific results which associate specific genes with complex behaviors. An important limitation of the study may be related to the number of gene polymorphisms analyzed.…”
Section: Discussionsupporting
confidence: 84%
“…Tryptophan hydroxylase-2 (TPH2) is the rate-limiting neuron-specific isoform catalyzing the rate-limiting step in biosynthesis of 5-HT in the brain, and its gene TPH2 is located on chromosome 12q21. This gene has an important role in regulation of the serotonergic system (Kautzky et al, 2019), aggressive behavior, cognitive control, and emotional regulation (Lehto et al, 2015;Waider et al, 2011). It is shown that certain allelic forms could promote lower anxiety, impulsivity, and aggressiveness (Laasa et al, 2017), but results are inconsistent (Gutknecht et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…72,73 In a recent study, 3 or more combined HTR1A and BDNF risk alleles associated increase 5-HT 1A receptor binding in cortical subregions. 74 In contrast, the COMT Val158Met rs4680 genotype oppositely altered the rs6295 association with interferon-induced depression. 75 Perhaps most intriguing is an interaction of the HTR1A rs6295 genotype with the phospholysine phosphohistidine inorganic pyrophosphate phosphatase (LHPP) gene in major depression, seen in Utah and Ashkenazi populations.…”
Section: Genetic Interactionsmentioning
confidence: 98%
“…The dominant expression of the BDNF gene is in the prefrontal cortex and hippocampus (e.g., Wishart et al, 2011). The functional polymorphism of the BDNF gene results from the substitution of one amino acid (Val) for another (Met) at codon 66 of the BDNF gene, which alters BDNF gene expression and leads to smaller hippocampal volume (Kautzky et al, 2019). Previous studies on associations between the BDNF gene polymorphism and cognitive functions have provided inconsistent findings (Sanwald et al, 2020).…”
Section: The Molecular Genetic Basis Of the Wcstmentioning
confidence: 99%
“…The BDNF gene is located on chromosome 11p14.1. It encodes a small protein that plays a key role in synaptic plasticity, regulating the number of synapses, axon growth, and hippocampal neurogenesis (Kautzky et al, 2019). The dominant expression of the BDNF gene is in the prefrontal cortex and hippocampus (e.g., Wishart et al, 2011).…”
Section: Latent Structure Of the Wcstmentioning
confidence: 99%